2023
DOI: 10.34172/japid.2023.002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bromelain in the control of postoperative pain after periodontal surgery: A crossover randomized clinical trial

Abstract: Background. This study aimed to compare the analgesic effects of Ibuprofen and bromelain after periodontal surgery. Methods. A double-blinded crossover clinical trial was conducted on 22 patients needing two crown lengthening surgeries without bone surgery or with limited bone surgery on two quadrants of the maxilla, with control and test sides. Each quadrant was randomly assigned to bromelain (500 GUD) or ibuprofen (400 mg). Immediately after the surgery and 6 hours after it, the first dose of the drugs was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Bromelain showed, through the results of this study, that it has the capacity to minimize postoperative trismus. Other studies have not shown the same results in terms of medication efficacy [16,17].…”
Section: Discussionmentioning
confidence: 86%
“…Bromelain showed, through the results of this study, that it has the capacity to minimize postoperative trismus. Other studies have not shown the same results in terms of medication efficacy [16,17].…”
Section: Discussionmentioning
confidence: 86%
“…One of the most interesting nutraceuticals, bromelain, is widely used for the prevention or co-management of numerous diseases that are characterized by the presence of inflammation, edema, and algesia. Although several clinical trials have demonstrated the efficacy of bromelain supplementation in the reduction in pain [ 20 ], inflammation [ 21 ], and edematous components [ 22 ], its commercial cost is high, while the isolation and purification of bromelain from pineapple (fruit, core, stems, and leaves) is an open issue, making up 70–90% of the final extract production cost [ 23 ]. Moreover, notwithstanding the advent of novel and viable protein purification methods such as membrane filtration, reverse micellar systems, aqueous two-phase extraction, and chromatographic techniques, as well as the development of new biotechnological processes aimed at reducing production costs, various limitations persist.…”
Section: Discussionmentioning
confidence: 99%